Hubungan Pemberian Air Susu Ibu (ASI) dengan Tumbuh Kembang Balita - Restu Octasila; Mardi Yana; Muniswatin Muniswatin (Jurnal Bidan Cerdas, 2019)
Growth and development of children from birth to adulthood, so it needs to be done early detection of developmental deviations. The results of the survey conducted at Puskesmas Parung Panjang there are 52 (0.5%) toddlers who get help MP-ASI because weight is very thin. Exclusive breastfeeding nutrition program at UPT Parung Panjang in 2016 which target 90%, but only reached 35.77%. The research method used is analytical descriptive with a Cross-Sectional approach with sampling technique with accidental sampling. The population used were children aged 6-60 months in Posyandu Bakti Husada, Puskesmas Parung Panjang with a sample of 41 respondents. The tool used is KPSP to detect the development, and table/chart BB/U and TB/U to measure the growth of children under five. The result of research from 41 respondents got the univariate results of good growth status as much 87,8% and less good as much as 12.2%. The result of the bivariate test showed statistically there was a significant relationship (p-value <0.05) between breastfeeding and infant growth. Conclusions and suggestions of the relationship of exclusive breastfeeding to the growth of babies, for mothers are expected to provide exclusive breastfeeding to babies and stimulate development early on.